Utilisation of Resources and Services in Libraries in Selected Public Libraries in South-West Nigeria - Ogunniyi, Samuel Oke; Ajakaye, Jesubukade Emmanuel; Akerele, Johnson A.; Adeleke, Dare Samuel (International Journal of Knowledge Content Development & Technology, 2025)
The public library is the university of the people. It is the library that is been founded and funded by local, and state governments in a particular community. Every category of people in the community is expected to enjoy the resources and services offered by the public library. It is observed that some public libraries in Nigeria are not living up to the expectations of their clientele in the area of rendering service to them. The study adopted a survey type of research. The population of the study consisted of library 136 users and 37 staff of Ekiti State Library Board, Ado Ekiti, Ekiti State, Ondo State Library Board, Akure, Ondo State, Ogun State Library Board, Abeokuta, Ogun State, Osun State Library Board, Osogbo, Osun State, and Oyo State Library Board, Ibadan, Oyo State. The study found that textbooks, reference resources, and storybooks were resources available in the library. reference services, lending services, and book reservations were the most services offered in the libraries and users were satisfied with these services. The prevalent challenges include no internet facility in the library; inadequate library resources; and lack of electronic information resources. Public libraries are the backbone of the community and the use of their resources and services impacts the development of that community. State Library Boards must look toward automating public libraries through the provision of electronic resources and necessary gadgets and must hold current and up-to-date titles to meet the needs of the public.